1993
DOI: 10.1007/bf00171893
|View full text |Cite
|
Sign up to set email alerts
|

Selecting inocula for the biodegradation of organic compounds at low concentrations

Abstract: The inability of many organisms to degrade pollutants at low concentrations is a problem when selecting inocula for bioremediation of sites with these low concentrations. Thus, a study was conducted to determine the effect of low concentrations of p-nitrophenol (PNP) on growth of four PNP-degrading bacteria and their abilities to metabolize low concentrations of the compound in culture and samples from an oligotrophic lake. PNP did not increase the growth rates of Flavobacterium sp. M4, Pseudomonas sp. K, Flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The results obtained in this study with DP-4 suggest that the biodegradation of extremely low concentrations of chemicals may be controlled by the presence of higher concentrations of other available substrates, as a number of studies have reported (7,12,25). The data also suggest that the inoculation of microorganisms to enhance the biodegradation of chemicals in polluted natural environments will not always give satisfactory results, because the concentrations of available substrates for microorganisms are generally extremely low in natural environments (11).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The results obtained in this study with DP-4 suggest that the biodegradation of extremely low concentrations of chemicals may be controlled by the presence of higher concentrations of other available substrates, as a number of studies have reported (7,12,25). The data also suggest that the inoculation of microorganisms to enhance the biodegradation of chemicals in polluted natural environments will not always give satisfactory results, because the concentrations of available substrates for microorganisms are generally extremely low in natural environments (11).…”
mentioning
confidence: 62%
“…In order to enhance the biodegradation of chemicals of environmental concern, the inoculation of microorganisms capable of degrading the chemicals has been reported (7,12). However, the attempts did not always produce desired results.…”
mentioning
confidence: 99%
“…concentration of the pesticide must not be so high as to be toxic, nor so low such that biodegradation does not proceed due to a lack of induction of appropriate degradative enzymes and uptake mechanisms, failure to induce sufficient enzyme activities, or problems in providing \ sufficient energy even for cell maintenance. [7,15] Figure ( …”
Section: Figure (2) Effects Of Various Ph Values On Growth Curve Of mentioning
confidence: 99%
“…Among the various xenobiotics that may have enhanced degradation in the rhizosphere, atrazine is a particularly good candidate since, like most hydrophobic compounds, it accumulates on clay and organic matter in the upper soil horizon occupied by plant roots. At normal application rates, it is present at relatively low concentrations that may preclude the growth and maintenance of an effective dégrader population size (48). This latter problem is particularly problematic for atrazine, which has a highly oxidized triazine ring that provides no energy for microbial growth (49) Thus atrazine-degrader organisms can only acquire energy by utilizing carbon in the side chains attached to the ring or by growth on other carbon compounds contained in soil organic matter or root exudates.…”
Section: Sandmann 1984 (8) 24-dmentioning
confidence: 99%